Indicators of Circular Economy: A Premise Towards a Green Economy - Luiza-Florentina ZAPUCIOIU; Maria Cristina STERIE (Communications of International Proceedings, 2022)
Circular Economy is a popular topic these days, covered in numerous publications, studied by a wide group of researchers, and, of course, guided by legal framework. The question of research is how the indicators of circular economy can reveal a pathway to joining from the linear economy and conventional one, towards circular, green economy. The aim of the research is to highlight the European statistics for being able to reduce the pollution and waste resources, as well as improve recycling rates and innovation.
Keywords: circular economy; indicators; sustainability; predictions